NAKHICHEVAN-ON-DON IN 1915-1919: IN THE GRIP OF THE FOOD CRISIS - S. Kazarov (Гуманитарные и юридические исследования)
The article examines the process of gradual deterioration of the food situation in the city of Nakhichevan-on-Don during the First World War, and then the revolution and the civil war. Until now, the period of independent existence of Nakhichevan-on-Don has not become the subject of special research, despite the fact that the materials at our disposal allow us to do this. In this article, the author for the first time changes the economic situation of the city from a prosperous to a critical one. The deterioration of the situation closely depended on the situation in the country’s economy as a whole. The city, which had never experienced a shortage of any product, gradually began to feel a shortage of bread, sunflower oil, sugar, and then meat and vegetables. The food crisis that gripped the city during the First World War and the Revolution was complemented by a fuel crisis, which manifested itself in chronic shortages of coal, oil and kerosene. In these difficult conditions, the city administration of Nakhichevan-on-Don used not only its old trade relations with individual regions and settlements of the country, but showed truly miracles of resourcefulness in search of agricultural products vital for the city. Nakhichevan merchants, who represented the majority of the city authorities, intensified all their old trade ties, which facilitated the supply of necessary food products to the city. At the same time, the city authorities tried to put things in order in the markets, fighting speculators and second-hand dealers. But even these measures did not always give a positive result.